The Influence of Brand Image, Product Quality, Promotion, and Purchasing System on Purchasing Decisions (Honda Automatic Motorcycle Purchase Decision in Yogyakarta City) - Syahril Askal; Alfina Zsazsa Naqiya; Agus Siswanto (Equity: Jurnal Ekonomi, 2024)
This study aims to analyze brand image, product quality, promotion, and purchasing system on purchasing decisions of Honda automatic motorcycles in the city of Yogyakarta. The population in this study were all users of Honda automatic motorcycles in the city of Yogyakarta. The sample in the study was 150 respondents. This study uses a quantitative approach. The data collection method uses a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple linear regression T test and F test. The results of this study indicate that brand image has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions, promotion has a positive and significant effect on purchasing decisions, purchasing systems have a positive and significant effect on purchasing decisions and show that brand image, product quality, promotion and purchasing systems have a simultaneous effect on purchasing decisions. The R square value of 0.659 indicates that the ability of the independent variable to explain the variation of the dependent variable is 65.9% and the remaining 34.1% is explained by variables outside the research model..